Level of Disability and Limitation of Shoulder Motion in Post Mastectomy at Hasan Sadikin Hospital Bandung in 2019 - Rachmawati, Nadya; Prabowo, Tertianto; Fathurrachman, Fathurrachman (Jurnal Penyakit Dalam Indonesia, 2020)
Introduction. Post-mastectomy complications in breast cancer patients can be a long-term disabilities such as limitation of shoulder function that only appears after several months to years after surgery and may remain for the rest of the patient’s life. This study aims to describe the level of disability and limitation of the shoulder joint’s range of motion in breast cancer patients following mastectomy at Hasan Sadikin Hospital, Bandung 2019. Methods. This research was conducted by using descriptive method with cross-sectional study design. Sampling technique using consecutive sampling method during one-month study period. Samples were post-mastectomy breast cancer patients who came to the Surgical Oncology Department of Hasan Sadikin Hospital Bandung on October-November 2019. Upper limb disability level obtained based on the results of quickDASH score filled by the patient while the range of motion of the shoulder joint measured by the researcher itself using a goniometer. Results. The QuickDASH scores from 84 patients studied, showed a median of 4.6 (range 0 - 59.1) with the majority falling in the category of minimum disability (score 1-20). The measurement of shoulder joint’s range of motion using goniometer showed a decrease in abduction on 52% of patients, decrease in flexion on 44% of patients, and decrease in external rotation on 20% of patients. Conclusions. The level of disability of the shoulder joint in the department of post-mastectomy Dr. Hasan Sadikin Bandung October-November 2019 showed the majority of minimum disability and limitation of motion of the shoulder joint occurs dominant abduction motion. Keywords: Breast cancer, mastectomy, quickDASH score, range of motion